2005
DOI: 10.1176/appi.ajp.162.5.883
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Prevalence and Stability of Individual DSM-IV Criteria for Schizotypal, Borderline, Avoidant, and Obsessive-Compulsive Personality Disorders: Toward a Hybrid Model of Axis II Disorders

Abstract: Objective-This study tracked the individual criteria of four DSM-IV personality disordersborderline, schizotypal, avoidant, and obsessive-compulsive personality disorders-and how they change over 2 years.Method-This clinical sample of patients with personality disorders was derived from the Collaborative Longitudinal Personality Disorders Study and included all participants with borderline, schizotypal, avoidant, or obsessive-compulsive personality disorder for whom complete 24-month blind follow-up assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
193
3
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(224 citation statements)
references
References 39 publications
17
193
3
8
Order By: Relevance
“…CLPS data have previously revealed the differential stabilities of PD symptoms (McGlashan et al, 2005), differential stabilities and predictive validities of trait and pathological personality models , the specificity of trait predictions (Hopwood et al, 2009), and the predictive validity of traits independent of PD status . Taken together, these results favor explicitly separating pathological disorder dimensions from normative trait dimensions and measuring both in the assessment of personality pathology.…”
Section: Recommendations For Dsm-5mentioning
confidence: 99%
“…CLPS data have previously revealed the differential stabilities of PD symptoms (McGlashan et al, 2005), differential stabilities and predictive validities of trait and pathological personality models , the specificity of trait predictions (Hopwood et al, 2009), and the predictive validity of traits independent of PD status . Taken together, these results favor explicitly separating pathological disorder dimensions from normative trait dimensions and measuring both in the assessment of personality pathology.…”
Section: Recommendations For Dsm-5mentioning
confidence: 99%
“…17, 27 McGlashan and colleagues 17 demonstrated overall improvement in BPD symptoms but also found that the rank order of symptom prevalence remains stable over time. In other words, the most prevalent BPD criteria, such as affective instability and anger, were least likely to remit and had trait-like qualities.…”
mentioning
confidence: 98%
“…17–19 It is commonly assumed that certain forms of personality pathology diminish or “burn out” by middle age. Some cross-sectional studies indicate that personality disorders are less prevalent among older adults, 20 but subthreshold pathology persists.…”
mentioning
confidence: 99%
“…26 Performance anxiety, loss of self-esteem and a reduced quality of life are prevalent in ED, 27 and underscore a high level of mental stress associated with sexual dysfunction. OC features, and consequent low ability to cope with potentially stressful circumstances, 28 might be surmised as a potential risk for ED, mostly in men with preclinical atherosclerosis, which show a more severely deranged erectile function. 18 Mental stress has been linked to an increased autonomic sympathetic activation 29 that results in an enhanced platelet activation and aggregability and increased circulating level of fibrinogen and thromboxane A2 with consequent risk for arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%